Gut Microbiota Mediates the Preventive Effects of Dietary Capsaicin Against Depression-Like Behavior Induced by Lipopolysaccharide in Mice - Xia, Jing; Gu, Li; Guo, Yitong; Feng, Hongyan; Chen, Shuhan; Jurat, Jessore; Fu, Wenjing; Zhang, Dongfang (Frontiers in Cellular and Infection Microbiology, 2021)
Capsaicin (CAP) is an active ingredient in chili pepper that is frequently consumed. It exerts various pharmacological activities, and also has potential effects on mental illness. However, its mechanism of antidepressant effects is still unclear. Based on the emerging perspective of the gut-brain axis, we investigated the effects of dietary CAP on gut microbes in mice with depression-like behaviors induced by lipopolysaccharide (LPS). C57BL/6J male mice (four weeks old) were given specific feed (standard laboratory chow or laboratory chow plus 0.005% CAP) for 4 months. During the last five days, LPS (0.052/0.104/0.208/0.415/0.83 mg/kg, 5-day) was injected intraperitoneally to induce depression. Behavioral indicators and serum parameters were measured, and gut microbiota were identified by sequencing analysis of the 16S gene. This study showed that dietary CAP improved depressive-like behavior (sucrose preference test, forced swimming test, tail suspension test) and levels of 5-HT and TNF-α in serum of LPS-induced mice with depression-like behaviors. In addition, CAP could recover abnormal changes in depression-related microbiota. Especially at the genus level, CAP enhanced the variations in relative abundance of certain pivotal microorganisms like Ruminococcus, Prevotella, Allobaculum, Sutterella, and Oscillospira. Correlation analysis revealed changes in microbiota composition that was closely related to depressive behavior, 5-HT and TNF-α levels. These results suggested that dietary CAP can regulate the structure and number of gut microbiota and play a major role in the prevention of depression.